The Wicked and the Logical: Facilitating Integrative Learning Among Introductory Computing Students - Stone, Jeffrey; Cruz, Laura (Teaching and Learning Inquiry, 2021)
Higher education has embraced integrative learning as a means of enabling students to tackle so-called “wicked” problems, i.e. problems that are sufficiently complex, contested, and ambiguous that conventional, disciplinary specific approaches are inadequate to address. However, challenges remain in defining integrative learning consistently and effectively, especially because the cognitive processes that make up an integrative learning experience are not understood fully. This mixed-methods study was designed to help understand how students perceive, navigate, and resolve challenges that require them to integrate knowledge of one “wicked” subject (sustainability) with the skills of a practice rooted in mathematical logic (computer programming); how they express their integrative learning through reflective writing; and how we gain a stronger understanding of this process through linguistic analysis. The findings suggest that some students demonstrated the ability to integrate computational reasoning skills into socially relevant contexts more successfully, confidently, and in more well-rounded ways than others, though success required ways of thinking that extended beyond programming. The findings also underscore the potential need for reconceptualizing integrative teaching and learning in fields that have problem-solving traditions rooted in less “wicked” solutions.